Anti-HIV Transcriptase Herbs: A Review - Hasan, Khomaini; N Ferdianti, Fine; P Y Paryati, Sayu (ACTA Medical Health Sciences, 2023)
To date, combination antiretroviral (ARV) medication is considered the most effective treatment for people infected with the Human Immunodeficiency Virus (HIV). The primary purpose of ARV administration is to reduce the viral load, thereby enhancing HIV patients' immunological condition and minimizing mortality from opportunistic infections. Nowadays, a combination of NRTI (nucleoside analog reverse transcriptase inhibitor) and NNRTI (non-nucleoside analog reverse transcriptase inhibitor) is accepted therapy for HIV patients. Both have a mechanism for inhibiting the reverse transcriptase (RT) enzyme during viral replication. Reverse transcriptase (RT) is an enzyme that plays a role in the reverse transcription stage of the virus reproduction process. HIV RT converts proviral RNA into DNA, and the copy infects the host or target cell. The use of RT inhibitors for HIV-infected patients is becoming more common. Many investigations were conducted on plants that have the potential to operate as anti-HIV RT. In this review, we go over some of the potential herbs that serve as RT inhibitors. In this literature review, a search was carried out with the help of several search engines that matched the criteria, namely reverse transcriptase herbal inhibitors for HIV. The author came to the conclusion that there were 18 plants with relatively high activity as anti-HIV medicines with varied traits and working mechanisms from 162 papers gathered based on keywords. Furthermore, the findings of this study will serve as the foundation for the development of anti-HIV herbs as well as a source of antiretroviral therapy ingredients in the future. DOI : 10.35990/amhs.v2n2.p96-108 REFERENCE (2019). Global HIV and AIDS statistics 2019 Fact Sheet. World AIDS Day 2019 Fact Sheet, 1(1), 1–6. World Health Organization. (2016). Integrating collaborative TB and HIV services within a comprehensive package of care for people who inject drugs: Consolidated guidelines (45 p.). Retrieved from: who.int/about/licensing/copyright_form/en/index.html Karyadi, T. H. (2017). Keberhasilan Pengobatan Antiretroviral (ARV). Jurnal Penyakit Dalam Indonesia, 4(1), 2–4. Kufel, W. D. (2016). Nucleoside Reverse Transcriptase Inhibitor (NRTI) Associated Macrocytosis. International Journal of Virology & AIDS, 3(1). Pau, A. K., & George, J. M. (2014). Antiretroviral therapy: Current drugs. Infectious Disease Clinics of North America, 28(3), 371–402. Schinazi, R., Kohler, J., & Kim, B. (2017). Reverse Transcription. Seitz, R. (2016). Human Immunodeficiency Virus (HIV). Transfusion Medicine and Hemotherapy, 43(3), 203–222. Poltronieri, P., Sun, B., & Mallardo, M. (2015). RNA Viruses: RNA Roles in Pathogenesis, Co-replication and Viral Load. Current Genomics, 16(5), 327–335. Marintcheva, B. (2018). Viral Tools for In Vitro Manipulations of Nucleic Acids. In Harnessing the Power of Viruses (pp. 27–67). Kuete, V. (2017). Allium sativum. In Medicinal Spices and Vegetables from Africa (pp. 363–377). Academic Press. Yamaguchi, Y., & Kumagai, H. (2019). Characteristics, biosynthesis, decomposition, metabolism and functions of the garlic odour precursor, S-allyl-L-cysteine sulfoxide. Experimental and Therapeutic Medicine, 15, 1528–1535. Divya, B. J., Suman, B., Venkataswamy, M., & Thyagaraju, K. (2017). A Study on Phytochemicals, Functional Groups and Mineral Composition of Allium sativum (Garlic) Cloves. International Journal of Current Pharmaceutical Research, 9(3), 42. Rouf, R., Jamal, S., Kumer, D., & Torequl, M. (2020). Antiviral potential of garlic (Allium sativum) and its organosulfur compounds: A systematic update of pre-clinical and clinical data. Trends in Food Science & Technology. Klopper, R. R., & Smith, G. F. (2013). Aloes of the world: When, where and who? Aloe, 50(1&2), 44–52. Mulaudzi, R. B. (2012). Pharmacological evaluation of medicinal plants used by Venda people against venereal and related diseases. Gómez-Cansino, R., et al. (2015). Antimycobacterial and HIV-1 reverse transcriptase activity of Julianaceae and Clusiaceae plant species from Mexico. Evidence-Based Complementary and Alternative Medicine, 2015. Valdiani, A., et al. (2012). Nain-e havandi Andrographis paniculata: A plenary review. Molecular Biology Reports, 39(5), 5409–5424. Jeeva, J. J. (2014). Andrographis paniculata: A review of its traditional uses, phytochemistry and pharmacology. Medicinal & Aromatic Plants, 3(4). Gurrapu, S. (2017). In vitro HIV-1 reverse transcriptase inhibition. European Journal of Biomedical and Pharmaceutical Sciences, November. Sanower Hossain, M., et al. (2014). A review of ethnobotany, phytochemistry, and pharmacology. The Scientific World Journal, 2014, 1–28. Patin, E. W., Zaini, M. A., & Sulastri, Y. (2018). Influence of dried temperature variation on tea leaf (Andrographis paniculata). 2018;4(1):251–8. Bonvicini, F., et al. (2018). Hemidesmus indicus extract inhibits herpes simplex replication. New Microbiologica, 41(3), 187–194. Turrini, E., et al. (2018). Antigenotoxic profile of Hemidesmus indicus on T lymphoblastic cells. Toxins (Basel), 10(2). Rastogi, J., & Rana, S. (2018). Economic importance of some invasive alien species in Uttarakhand, India. Advances in Biores, 9(91), 59–65. Esposito, F., et al. (2017). Multi-target HIV-1 activity of Hemidesmus indicus decoction. Pathogens and Disease, 75(6), 1–5. Kiren, Y., et al. (2014). Justidrusamides A-D from Justicia gendarussa. Journal of Natural Medicines, 68(4), 754–758. Zhang, H. J., et al. (2017). Inhibitor of drug-resistant HIV-1 strains from Justicia gendarussa. Journal of Natural Products, 80(6), 1798–1807. Widiyanti, P., et al. (2015). Reverse transcriptase inhibition by gendarussin A from Justicia gendarussa. Indonesian Journal of Tropical and Infectious Disease, 5(5), 136. Widodo, A. (2019). Prediction of pharmacokinetics and HIV-1 protease inhibitor activity of Justicia gendarussa leaves. Journal of Pharmaceutical Science & Practice, 6(1), 1–5. Gupta, S., & Gupta, P. (2020). The genus Calophyllum: Ethnomedicinal uses and pharmacology. Bioactive Natural Products in Drug Discovery, 215–242. Bernabé-Antonio, A. (2014). Biological importance of phytochemicals from Calophyllum brasiliense. Annual Research & Review in Biology, 4(10), 1502–1517. Kumari, N., et al. (2015). Curcumin A: A novel inhibitor of HIV-1. Drug Design, Development and Therapy, 9, 5051–5060. Dwevedi, A., & Dwivedi, R. (2016). Pharmacognosy Reviews. Bortolotti, M., et al. (2019). Momordica charantia as anti-inflammatory. Frontiers in Pharmacology, 10(May), 1–9. Khan, M., et al. (2023). Anti-HIV-1 activity of MoMo30 protein from Momordica balsamina. Virology Journal, 20(1), 1–15. K., & Mohan, V. (2009). In vitro propagation of Phyllanthus urinaria. Researcher, 1, 56–61. Sigidi, M. T., et al. (2017). Anti-HIV and cytotoxicity properties of Venda plants. Indian Journal of Traditional Knowledge, 16(4), 545–552. Ghosh, B. M., et al. (2022). Medicinal insights on Phyllanthus amarus. Nucleus (India), 65, 437–472. Chinsembu, K. C. (2019). Chemical diversity of HIV-1 reverse transcriptase inhibitors from plants. Brazilian Journal of Pharmacognosy, 29(4), 504–528. Narayan, L. C., et al. (2013). Emerging need for phytopharmaceuticals in HIV treatment. Journal of Pharmaceutical Research, 6(1), 218–223. Ramadass, N., & Subramanian, N. (2018). Phytochemical screening of neem (Azadirachta indica). International Journal of Zoological Studies, 3(1), 209–212. Awah, F. M., et al. (2011). Anti-HIV and immunomodulatory potentials of neem. African Journal of Pharmacy and Pharmacology, 5(11), 1353–1359. Ye, X. J., & Ng, T. B. (2011). HIV-1 reverse transcriptase inhibitory proteins from mini-black soybean. Evidence-Based Complementary and Alternative Medicine, 2011. Fang, E. F., et al. (2010). Lectin from Phaseolus vulgaris with anti-HIV-1 activity. Journal of Agricultural and Food Chemistry, 58(4), 2221–2229. Nworu, C. S., et al. (2013). Moringa oleifera extracts inhibit HIV-1 infectivity. African Journal of Biotechnology, 12(30), 4866–4873. Ndhlala, A. R., et al. (2016). HIV management and pharmaco-synergy of Moringa oleifera. Planta Medica, 82(S 01), s1–381. Behbahani, M., et al. (2014). Anti-HIV-1 activity of kaempferol from Securigera securidaca. Research in Pharmaceutical Sciences, 9(6), 463–469. Jiang, Y., et al. (2010). Natural product inhibitors of HIV-1 reverse transcriptase, protease and integrase. Mini Reviews in Medicinal Chemistry, 10(14), 1331–1344.